1996
DOI: 10.1016/s0277-3791(96)00071-6
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional factors controlling changes of coastlines in Southern Iberia (Spain) during the holocene

Abstract: -The interaction between global (glacio-eustatic sea-level rise) and regional factors (oceanographic and tectonic) has controlled the evolution of coastline during the Holocene in Southem Iberia.At ca. 10,000 14C years BP a deceleration of relative sea-level rise took place both in the Atlantic and Mediterranean littorals, with a maximum transgression at 6450 14C years BP. In subsiding areas (present tidal flats) estuaries illustrate a clear marine influence recorded both in sediments and the fauna while in up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 2 publications
5
68
0
4
Order By: Relevance
“…1). The best, more continuous results were obtained in Guadalete (Goy et al , 1996;Dabrio et al, 1999Dabrio et al, , 2000 and OdielTinto estuaries. In the Guadalquivir estuary, the biggest of all, results are still fragmentary (Zazo et al, 1999c), and reconstructions of the fossil infill of the paleo-valley are most difficult at present owing to the lack of dated cores and complex tectonic activity.…”
Section: Estuariesmentioning
confidence: 91%
See 3 more Smart Citations
“…1). The best, more continuous results were obtained in Guadalete (Goy et al , 1996;Dabrio et al, 1999Dabrio et al, , 2000 and OdielTinto estuaries. In the Guadalquivir estuary, the biggest of all, results are still fragmentary (Zazo et al, 1999c), and reconstructions of the fossil infill of the paleo-valley are most difficult at present owing to the lack of dated cores and complex tectonic activity.…”
Section: Estuariesmentioning
confidence: 91%
“…These phases are also noted in the rates of sedimentation measured in estuaries, where the processes of vertical aggradation gave way to those of progradation, particularly since 2400 cal a BP. More open marine conditions occurred at '"'-'8000 cal a BP (Goy et al, 1996). Consequently, the coastal archives do not record the stillstands or sea level fa lIs during the cool Younger Dryas episode and Holocene Bond event at '"'-'8.2 cal ka BP seemingly recognisable in the shelf.…”
Section: U5mentioning
confidence: 96%
See 2 more Smart Citations
“…A major advance has been the recognition and refinement of a chronology of events of and erosion of beaches after the maximum in the area 6500 14C years BP, Zazo et al, 1994a). In the best developed case (Goy et al, 1996, found in the Atlantic-Mediterranean area (Roquetas, SE Westem each barrier system includes four morpho-sedimentary units named spit barrier units Hl to H 4 . Discrete sets of beach crests and swales on the surface of each unit are separated by erosional surfaces andj or particularly swales called gaps.…”
mentioning
confidence: 99%